Effect of tillage systems on the earthworm population in forage maize - Aldaco-Gómez, Daniel; Cadena Zapata, Martín; Zermeño-González, Alejandro; López-López, Juan Antonio; Cerna-Chávez, Ernesto (Ecosistemas y Recursos Agropecuarios, 2023)
Earthworms are an essential component of the soil macro fauna to maintain its quality. Tillage can negatively affect earthworm populations; environmental factors are vital for their abundance or decline. This research aimed to evaluate the effect of tillage systems on the earthworm population in the presence of environmental factors such as temperature, precipitation, and relative humidity in forage maize. Direct Seeding (SD), Vertical Tillage (LV) and Conventional Tillage (LC) were evaluated in complete blocks at random in plots of 6 x 40 m with three replications. The number of worms was measured during summer-fall 2020 and 2021, before tillage, after sowing, mechanical weed control, and harvest. LC and LV caused a decrease in individuals after their application. On the contrary, SD promoted an increase in the number of individuals. At SD treatment, more individuals were reached when temperature and precipitation were optimal.